Editorial of Conspiracy Hate and Insecurity: The Algerian Military Magazine ‘El-Djeich’ as a Case - Mliless , Mohamed; Handoko (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2021)
This research critically analyzes 10 editorials written in French that the Algerian army magazine (El-Djeich) published from January 2021 to October 2021, a peak time for the army to reinforce its threatening discourse against Morocco (the classical enemy of Algeria). It attempts to explore how the editorials employ a conspiracy narrative to represent Morocco as a country that has been waging wars and threatening its stability. The editorials aim to construct an ‘outer enemy’ to shift the public opinion from political, social, and economic problems that the appointed political leadership fails to solve. More than that, the editorials try to reestablish the image of the army underestimated by the social protestation Hirak which claims a ‘civil and not a military state’. Since the 16th of February 2019, the Hirak has been claiming that the army should return to its barracks and take care of the security of the country's borders instead of interfering in social, political, and economic affairs. The theoretical framework of this study was based on van Dijk’s model (van Dijk, 1985, 1989, 1993, 1998a, 1998b, 2000, 2004, 2006) to treat the texts as a voice of the Algerian army that violently attacks Morocco, amidst high tensions between the two countries, accusing the kingdom of instrumentalizing ‘conspiracies’ and waging ‘cyber-attacks' against Algeria. Relying on critical discourse analysis (CDA), the many linguistic constructions identified in the editorials reflect that the stand of the army and the political leadership towards Morocco are unfounded and fallacious. For instance, the findings of this research identified a pattern of argumentation based on erroneous allegations that the magazine of the army attributed to Morocco. Devoid of any proofs, the editorials have portrayed Morocco as a ‘threat to the country’. As a matter of fact, the study assumes that the magazine of the army uses editorials to rally the population against an external enemy and to divert the attention of the Algerian population from real internal problems. Indeed, the challenge for the Algerian military leadership is to convince the Hirak partisans, who strongly denounce the interference of the army in Algerians life, that the national army is the only institution that can stop an external enemy (Morocco) which threatens their well-being than do internal economic, political and security challenges.